(NmATEMATI^ESKIE RE[ENIQ TRUDNOFORMALIZUEMYH GEOLOGI^ESKIH ZADA^ (B/s - (NrAEWSKIJ(B, (NwIKTOR `RXEWI^s; (NrODIONOW(B, (Nd(B.(Na(B.s ((NmOSKWA (B:s (NnAUKA(B,s, 1987)
(NbIBLIOGR(B.: (NS(B. 115-117 (84 (NNAZW(B.)s
(Nwnii \KONOMIKI MINER(B. (NSYRXQ I GEOL(B.-(NRAZWED(B. (NRABOTs
Keywords: (NgEOLOGIQs; (NmATEMATI^ESKIE METODYs